HCG is more effective than the GnRH agonist buserelin for inducing the first ovulation of the breeding season in mares. (9th May 2021) - Fanelli, Diana; Tesi, Matteo; Rota, Alessandra; Beltramo, Massimiliano; Conte, Giuseppe; Giorgi, Mario; Barsotti, Giovanni; Camillo, Francesco; Panzani, Duccio
Abstract: Background: Human Chorionic Gonadotropin (hCG) and Gonadotropin Releasing Hormone agonists (GnRHa) are routinely used to induce ovulation in mares. However, GnRHa efficacy in transitional mares has been suggested to be low. Objectives: The aims of this study were as follows: (a) to compare the efficacy of hCG and GnRHa in inducing the first ovulation of the breeding season and (b) to evaluate the correlation between ovulatory response, uterine oedema and teasing score at the time of treatment during the early or late transitional phase. Study design: Randomised controlled superiority trial. Methods: Mares in winter anoestrus were treated with sulpiride when at least two follicles reached a diameter of 25 mm. The day after the follicle reached 35 mm in diameter, mares in oestrus were treated with GnRHa buserelin (N = 29) or hCG (N = 33) and checked daily for ovulation. Results: More mares (30/33, 90.1%) ovulated when the first ovulation after winter anoestrus was induced with hCG, than with GnRHa, (11/29, 38.0%) ( P  = .0001). Ovulation rate was lower in mares that did not show uterine oedema and full acceptance of the teaser stallion for at least three days before the treatment (32/41, 78% vs 9/21, 42.9%) P  = .01. Main limitations: Plasma LH and oestrogen concentrations were not performed. Conclusions: These results demonstrate that hCG was more effective than GnRHa for inducing ovulation in the first cycle after winter anoestrus. Uterine oedema and behavioural signs of oestrus, for at least three days before the treatment, were predictors for a positive response to ovulation induction.